Pengelolaan Pembelajaran Bahasa Inggris Berdasarkan Kurikulum 2013 Di Kelas VIII SMP Negeri 1 Delanggu, Kabupaten Klaten - Sukrowati, Ida, Dr. Maryadi, M.A, Dr. Wafrotur Rohmah ,M.M (2016)
This study aims at; 1). Describing the characteristics of the preparation of learning English is based Curriculum 2013 in Class VIII SMP N 1 Delanggu, Klaten regency; 2).Describing the characteristics of the preparation of teachers in the teaching of English based Curriculum 2013 in Class VIII SMP N 1 Delanggu, Klaten regency; 3). Describing the characteristics of the implementation of English language learning based Curriculum 2013 in Class VIII SMP 1 Delanggu, Klaten regency; 4). Describing the characteristics of the evaluation of learning English is based Curriculum 2013 in SMP N 1 Delanggu, Klatenregency. This type of qualitative research methods research design using an ethnographic approach. This research was conducted at SMPN 1 Delanggu as is one of the schools curriculum implementation pilot project in 2013 in the district of Klaten. The data used in this study consisted of primary data and secondary data. Data analysis technique used in this research is the analysis of interactive model. While data Collenting method uses ; Indepth Interview, Observation, and Documentation.The survey results revealed that, 1). Teacher subjects in English is already preparing a lesson plan curriculum in 2013 before the new school year begins, although not yet complete and perfect. Since 2013 learning curriculum was applied in accordance with the rules of implementation of learning In English that have been enacted; 2). Preparation of teachers of English based Curriculum 2013 in Class VIII SMP N 1 Delanggu, the teacher's role is very important in learning, as manager of the learning objectives will be achieved if managed properly. Teachers should be ready to increase its competence, it is recommended always focus, both in the classroom and MGMPs activities with teachers from the school curriculum piloting 2013; 3). Implementation of learning: (a) all teachers are implementing learning in accordance with the RPP (b) the objectives listed RPP in accordance with the theme, the material in the syllabus and the students' books. (c) material not only based on student and teacher handbooks course, can also be taken from the internet. (d) Approaches, Models, Strategies and learning methods used to use a wide range of variations to suit the purpose of learning materials in 2013 a student-centered curriculum, fun, creative, innovative, scientific approach. (e) the teacher uses Infrastructure and Learning Tools are already available, also take advantage of other learning tools, both of which encountered on his way from home to school. (f) the teacher has conducted an assessment in accordance with curriculum guidelines in 2013, the assessment of aspects of knowledge to aspects of skills and attitudes, 4). The school principal also evaluated by means of administrative supervision and in the classroom. There are three categories of obstacles from the teacher, curriculum polemics, and of student learning. To overcome these obstacles teachers still need continuous training of the competent authorities.